ROLE OF PLANT GROWTH REGULATORS IN CALLUS INITIATION AND PLANTLETS REPRODUCING OF TWO ALFALFA CULTIVARS - & Ali, Hamza (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
An experiment was conducted at the central lab of Graduate studies - College of Agriculture, University of Baghdad during 2015-2016. The objective was to study the effect of growth regulator on inducing callus from embryos of two alfalfa cultivars (PAC-78001 and local) variety by tissue culture technique using factorial experiments according to CRD. Seeds sterilized by NaOCl at 4.5% for 15 minutes, then, cultured on MS media free of growth regulators to embryo induced. The embryos were cultured on MS media at different concentrations of 2,4-D (0, 1, 2, 3 and 4) mg Li-1. Induced callus from embryos was cultured on MS media supplementing with Kin. at 0, 0.25, 0.50, 0.75 and 1 mg Li-1 to determine the best concentration. The results showed that best concentration of 2,4-D and Kin were 2 and 0.5 mg L-1 respectively which  gave highest callus fresh weight and callus dry weight (204.65 and 21.50) mg Li-1, respectively. BA at 2 mg Li-1 gave the highest plantlets reproducing from callus amounted 5.5 vegetative growth tube-1.